One-stop shopping behavior, buyer power, and upstream merger incentives - Irina Baye; Vanessa von Schlippenbach; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We analyze how consumer preferences for one-stop shopping affect the (Nash) bargaining relationships between a retailer and its suppliers. One-stop shopping preferences create 'demand complementarities' among otherwise independent products which lead to two opposing effects on upstream merger incentives: first a standard double mark-up problem and second a bargaining effect. The former creates merger incentives while the later induces suppliers to bargain separately. When buyer power becomes large enough, then suppliers stay separated which raises final good prices. We also show that our result can be obtained when wholesale prices are determined in a non-cooperative game, under two-part tariffs and when products are substitutable.
Keywords: L12; L22; L42; 330; One-Stop Shopping; Buyer Bower; Upstream Merger